Be my guest : - O'Hara, Francis (Cambridge University Press, 2002)
Be My Guest is a language course for in and pre-service students of Hotel English at the elementary to lower intermediate level. It consists of Student's Book, Teacher's Book and audio material on either cassette or audio CD. Written by an author who has considerable experience of teaching this kind of student in France, it focuses on building fluency and vocabulary, and improving grammatical and pronunciation accuracy. The 15 units of the course are each divided into two easy-to-use double page spread lessons and cover the range of communicative situations that hotel workers may find themselves in.